The Effect of Pricing Strategies on Client Retention Rates for Small to Medium-Sized Auditing Firms - Phung, Viet Ha; Pham, Huy Hung; Tran, Binh Minh (International Review of Management and Marketing, 2024)
The study aims to identify which pricing strategies are most effective in retaining clients, with the purpose of providing practical guidance for audit firms in Vietnam to enhance their competitiveness and sustainability. The study used quantitative methods, using survey data collected from 257 experts in 132 small and medium-sized auditing companies (with an annual revenue of less than VND 300 billion) in the Vietnamese auditing industry. Hypotheses were tested using structural equation modeling to analyze the relationships between pricing strategies and client retention rates. The results reveal that Value-based pricing (VBP) and Dynamic pricing (DYP) strategies have a positive and statistically significant impact on client retention, while Cost-plus pricing (CPP) and Competition-based pricing (CBP) do not show significant effects. These findings are significant as they highlight the evolving nature of the Vietnamese audit market, emphasizing the growing importance of value communication and pricing flexibility. The implications suggest that small and medium-sized audit firms in Vietnam should focus on developing more sophisticated, value-oriented pricing strategies to improve client retention and strengthen their market position. This research contributes to both theoretical understanding and practical application in the field of audit pricing in emerging markets.